The Role Of Islamic Religious Education Supervisorsin Improving The Quality Of Islamic Religious Education Learning In Salaman - Rifki Abdul Aziz; Laili Syarifah; Dahlia (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
One element that has a strategic role in improving the quality of PAI learning is the PAI supervisor. PAI supervisors are responsible for ensuring that the Islamic learning process takes place effectively following established standards. One of the duties of supervisors of Islamic religious education is to monitor national PAI standards, which is vital in maintaining the quality of learning. This research aims to determine the role of Islamic Religious Education supervisors in improving the quality of Islamic Religious Education learning in Salaman District, Magelang Regency. Researchers used a qualitative approach with collection methods in the form of interviews, observation, and documentation. The data analysis method uses Miles and Huberman's interactive (flow) model, which includes data reduction, data display, and drawing conclusions or verification to obtain data in-depth and interactively. The results of this research indicate that the role of PAI Supervisors in improving the quality of Islamic Religious Education learning in Salaman District, Magelang Regency, is 1) Preparation of supervisory work programs. 2) Collecting data on teachers' real needs and problems faced by teachers. 3) Activate the Madrasah Islamic Religious Education Working Group. 4) Maximize the implementation of supervisory duties. 5) Providing technical support for learning management and good learning examples.